2013
DOI: 10.5812/aapm.9246
|View full text |Cite
|
Sign up to set email alerts
|

Post Tonsillectomy Pain: Can Honey Reduce the Analgesic Requirements?

Abstract: BackgroundTonsillectomy with or without adenoidectomy is one of the most common surgical procedures performed worldwide, especially for children. Oral honey administration following tonsillectomy in pediatric cases may reduce the need for analgesics via relieving postoperative pain.ObjectivesThe aim of this study was to evaluate the effects of honey on the incidence and severity of postoperative pain in patients undergoing tonsillectomy.Patients and MethodsA randomized, double blind, placebo controlled study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(63 citation statements)
references
References 23 publications
2
60
0
1
Order By: Relevance
“…They observed that post-operative honey administration reduced post-operative pain in patients (10). …”
Section: Discussionmentioning
confidence: 99%
“…They observed that post-operative honey administration reduced post-operative pain in patients (10). …”
Section: Discussionmentioning
confidence: 99%
“…Only five of the 36 included trials were assessed as being at overall low risk of bias . Eleven were assessed as being at unclear risk of bias, and all remaining studies were assessed as being at overall high risk of bias. Details on quality assessment are presented in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…They administered honey locally immediately after dissection followed by oral honey and found that the wound healing was significantly faster in the treatment group in both tonsillar fossae compared to the control group (left: p-value = <0.001; right: p-value = <0.001). 9 Boroumand et al in their study observed that the difference between acetaminophen and acetaminophen plus honey groups was statistically significant both for visual analogue scale (VAS), and number of painkillers taken within the first three postoperative days. The consumption of painkillers differed significantly in every five postoperative days.…”
Section: Bar Diagram Showing Mucosal Healing In Group a And B N=78: 2x39mentioning
confidence: 96%